2016
DOI: 10.1080/01904167.2016.1187748
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional response of seedling tomato plants under different lighting treatments

Abstract: In order to describe the effect of complementary artificial light supply on the nutrient status of tomato seedlings, fluorescent lamps were compared each others. Nitrogen (N), phosphorus (P), and potassium (K) concentrations were measured (mg g 1 dry matter). Blue, red and far-red relationships were established. The N, P and K higher concentration and uptake have been found under high efficiency fluorescent lamps. Phosphorus uptake increasing was observed at high levels of irradiation. Potassium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…However, the in-depth mechanisms of BRs-induced stress tolerance still remain largely unknown. In nature, the first reaction of plants to biotic or/and abiotic stress is a decrease in photosynthesis, followed by plant growth retardation and loss of yield [52]. In the present study, exogenous application of EBR alleviated chilling-stress-induced decreases in plant growth (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…However, the in-depth mechanisms of BRs-induced stress tolerance still remain largely unknown. In nature, the first reaction of plants to biotic or/and abiotic stress is a decrease in photosynthesis, followed by plant growth retardation and loss of yield [52]. In the present study, exogenous application of EBR alleviated chilling-stress-induced decreases in plant growth (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the activity of nitrate reductase is influenced by the total radiation, as reported by Fallovo et al [40], which involves a decrease in nitrate concentration due to its reduction, which leads to a high level of nitrogen uptake and the consequent high level in leaves. Almansa et al [41] also reported an increase in N concentration in tomato seedlings grown under lamps with high blue spectrum values, which could be explained by the high activity of nitrate reductase in plants grown under blue light conditions, as proposed by Azuara and Aparicio [42]. The highest K concentration in roots and leaves in plants grown under TLD lamps can be also related with the high values of blue light radiated by the lamps.…”
Section: Discussionmentioning
confidence: 75%
“…The N concentration did not vary in the different organs of the plants under different light treatments. Different results were obtained by Almansa et al [33] who reported an increase of N concentration in tomato seedlings grown under lamps with high values of blue radiation.…”
Section: Discussionmentioning
confidence: 61%